Kepercayaan Diri pada Mahasiswi Pengguna Kosmetik di Fakultas Ilmu Pendidikan Universitas Negeri Semarang - Aulya Rahmawati; Muslikah (ILIN Institute, 2021)
This study is a qualitative research with a phenomenological approach which aims to describe the self-confidence of female students who use cosmetics. The subjects in this study were female students who were in their late teens with an age range of 18-21 years who studied at the Faculty of Education, Semarang State University as many as 3 people. Research subjects were selected by purposive sampling. The data obtained using non-test techniques, namely the interview method. The results showed that the image of self-confidence that appears in young women using cosmetics is that they become more positive in seeing themselves.